RIB FIXATION VERSUS CONSERVATIVE MANAGEMENT OF RIB FRACTURES IN TRAUMA PATIENTS - Majeed, Farhan Ahmed; Zafar, Usama; Imtiaz, Tashfeen; Shah, Syed Zahid Ali; Ali, Ahmad; Mehmood, Umer (Journal of Ayub Medical College Abbottabad, 2018)
Background: 10-15 % of trauma patient have chest injuries. There is a paradigm shift in the last two decades towards rib fixation from conservative management. Rib fixation results in immediate pain reduction in patients. Although rib fixation shows promising results, conservative management is still preferred. Methods: The study was carried out in CMH Lahore from Jan 2017 to March 2018. It was a Controlled Prospective study. Convenient sampling was used. 43 patients are included in the study. Patients with four or more fracture ribs were included. Patients followed at one, two and three months with spirometery/X-ray /clinical response. Rib fixation was done in 21 patients while 22 were managed conservatively. Patients were given choice of both the management options and treated as per their choice resulting in two groups. Results: Mean age of patients is 51.35 years. Majority of them were males (86.05%), had haemothorax as confirmed with CT scan (69.80%) and unilateral fracture (79.10%). 7.40% have flail segment. Operative group shows statistically significant improvement in the recovery to work and less post operative pain when compared to control group. There were no statistical differences among variables such as pre-operative severity and pain index, length of hospital stay, number of days for ventilator support and post op FEV1. There is statistically significant reduction in pneumonia (p <0.05), Acquired respiratory distress syndrome (ARDS) (p <0.05), ventilatory support greater than 1 day (p < 0.05) but there is no statistically significant reduction in Conclusion: Rib fixation should be performed early after trauma as it decreases pain, lessens complications and facilitate early recovery to work . Keywords: Rib fractures; titanium plates; fixation; trauma